GE_GERICHTE C/5262/2012 vom 20. Juni 2013 - GE Cour de justice (2013)
BAIL À LOYER; FRAIS ACCESSOIRES; CALCUL; AVIS DE MAJORATION DE LOYER | CO.257a.1; CO.257a.2; CO.257b.1; CO.269d.1; CO.269d.2; OBLF.19